SOFTWARE DEFECT PREDICTION USING EFFICIENT CLASSIFICATION ALGORITHMS - A.J, Anju; Judith, J.E. (International Journal of Advanced Science and Technology, 2019)
The reliability of the software can be understood using the recurrence and the development of failures or it could be recognized by framework accessibility. Software can be classified as many forms such as system software, application software, shareware, literate, freeware public domain etc. Nearly, all the frameworks used to have faults and these faults results in the failure. Inorder to understand these faults, some software fault prediction is used. The main aim of these method is to predict the errors and their cause before it occurs. This article mainly discusses about the techniques which are available for the prediction of error and gives the information to understand about the data mining with NASA MDP data sets.